Treatment of Hallux Rigidus: Comparison of Hemiarthroplasty with Cartiva Implant, Allograft Interpositional Arthroplasty, and Arthrodesis. Issue 4 (November 2022) - Sanii, Ryan; Phan, Kevin; Krumm, Drew B.; Patton, Daniel J.; Madden, Tyler; Anderson, John G.; Maskill, John D.; Bohay, Donald R.; Padley, Michelle A.; Patthanacharoenphon, Cameron G.
Category: Midfoot/Forefoot; Other Introduction/Purpose: Hallux Rigidus (HR) can cause pain with motion, enlarged joint, decreased joint space, subchondral sclerosis, osteophyte formation and restricted joint mobility, limiting patient physical activity. A modern technique for the treatment of HR is 1st MTP hemiarthroplasty with the use of a Cartiva synthetic cartilage implant. The Cartiva implant is designed to imitate natural cartilage; this allows patients to maintain motion in the 1st MTP joint. Current scientific literature reporting early outcomes of the procedure is sparse and mixed. This discrepancy and the overall scarcity of data indicates the need for further analysis. The purpose of this study is to compare improvement in VAS with 1st MTP hemiarthroplasty with the Cartiva implant, allograft interposition arthroplasty and fusion in patients who failed conservative management or cheilectomy. Methods: This study evaluated subjects who underwent interpositional arthroplasty, arthrodesis, or hemiarthroplasty with the Cartiva implant from January 2008 to April 2020, with a minimum of one year documented follow-up. All subjects were 18 years of age and older, diagnosed Hallux rigidus with pain, had a decrease in 1st MTP motion, and had X-ray findings consistent with decreased joint space. Patient data collected includes age, gender, ethnicity, occupation, height, weight, BMI, diabetes status, rheumatoid arthritis status, smoking, co-morbid conditions, medication, activity of choice, duration of symptoms, and operative data. Pre-operative and post- operative Visual Analog Scale (VAS) pain scores were compared between groups. Pain, function, and alignment between groups were also evaluated, pre-operatively and post- operatively, using the AOFAS Midfoot Scale. Secondary objectives evaluated include surgical complications, surgical revision, and X-rays. Results: One hundred patients with 12 months of post-operative follow-up were included in this study: 52 hemiarthroplasty with Cartiva implant patients (Group A), 24 arthrodesis patients (Group B), and 24 interpositional arthroplasty patients (Group C). The mean age of patients was 57.12 years (range 35-95). Average VAS pain scores for Group A was 3.78 (0-9), for Group B was 2.71 (0-10), and Group C was 3.67 (0-8). The average AOFAS score for Group A was 63.36 (30-95), for Group B was 60.98 (32- 83), and Group C was 60.13 (31-83). Pre-operative average VAS pain scores were 4.86 (Group A), 2.32 (Group B), and 5.58 (Group C). Post-operative average VAS pain scores were 2.69 (Group A), 0.91 (Group B), and 1.75 (Group C). Pre-operative average AOFAS scores were 59.52 (Group A), 48 (Group B), and 47.25 (Group C). Post-operative average AOFAS scores were 67.20 (Group A), 73.96 (Group B), and 73 (Group C). Conclusion: Preliminary data shows the greatest reduction in VAS pain scores in the interpositional arthroplasty group. The greatest improvement in derived AOFAS score was seen in the arthrodesis and interpositional arthroplasty groups, indicating a better overall combination of post-operative pain, function, and alignment when compared to patients who underwent hemiarthroplasty with Cartiva implant. While this study is not yet complete, it appears that hemiarthroplasty with Cartiva implant may allow patients to maintain motion in the 1st MTP joint, but at the cost of increased post-operative pain.